Variação sazonal da salinidade em dois Neossolos Flúvicos de texturas diferentes - Hilaire, Paul-Émile (2018)
In arid and semi-arid areas, salinity and sodicity are common problems, and there are few studies about the temporal variation of attributes in the profile of these soils, mainly in the semi-arid region of Brazil. This work aims to evaluate the evolution of the parameters related to salinity in the 1:1 soil:water extract in different periods of humidity (dry and rainy) in twosoils (Entisol Typic Torrifluvents - ETT and Entisol Sodic Torriarents - EST) located at the Vale do Curu Experimental Farm, Pentecoste, Ceará. After physical and chemical characterization of the horizons of both soils, 6 collections of soil samples were performed at 0-5, 5-15, 15-25, 25-40 and 40-60 cm dephts (3 in the dry season and 3 in the rainy season) in order to obtain the 1:1 extract (soil:water) and analyze the variables CE1:1, pH, soluble cations and anions. For all variables, descriptive statistical analysis was performed by determining mean, median, maximum, minimum, standard deviation and coefficient of variation. In both soils, the variables were compared inside the studied layers and in the profile for both periods. Considering the profile, it was observed that most of the variables showed asymmetric distribution, whereas in the layers the distribution was normal. The pH values varied little in the soil profile and had lower CV (between 5.45 and 6.93%). Electrical conductivity, calcium, potassium, and chloride showed the highest values in the first layer (0-5 cm) and also high CV(> 62%). The soluble sodium concentration did not change significantly in dry and humid periods due to the great sodium mobility which was controlled by irrigation in the NFET. On the other hand, in the NFST, sodium and chloride concentrations in the superficial layer were maintained low due to the dilution by rainwater and surface water movement, whereas in the dry period it was caused by the low sodium contribution from the lower layers due to their low hydraulic conductivity. The pH values in the NFST, relatively low for a sodic soil, indicate that it is a soil under degradation.